Design of a VR/AR Environment for Service Prototyping - Kekäle, Tauno; Helo, Petri; Stanisauskaite, Vaiva; Lammi, Miia (Sekvoyija, 2020)
Open innovation, especially in new services, places emphasis in co-creation ability for development processes. This becomes easier through digitalisation, as especially Virtual Reality technologies have been used for applications from product design to production simulation, trainings and marketing of solutions. This paper presents the background and specification of a service prototyping co-creation laboratory facility, built for testing industrial service concepts in virtual reality environments, called CoProtoLab.
Keywords: open innovation; servitization; virtual reality; business models; digitalisation; fi=Tuotantotalous|en=Industrial Management|